The Tragedy of Rara Kuning in Wayang Timplong: A Semiotic Analysis Based on Moral and Character Education - Yana, Anggun Mega Yuli; Haryanto, Eko; Purnomo, Sucipto Hadi (Universitas Muhammadiyah Enrekang, 2025)
The Wayang Timplong performance, as a traditional art form distinctive to East Java, serves as a cultural symbol that can be analyzed through a semiotic approach. This study aims to examine the denotative, connotative, and mythical meanings in the play “The Tragedy of Rara Kuning”, which was broadcast on the Asthabrata Media YouTube channel and performed by the puppeteer Ki Badaralam. The research employs Roland Barthes’ semiotic theory as its analytical framework. The findings indicate that the main narrative of The Tragedy of Rara Kuning by Ki Badaralam contains classical elements commonly found in folk traditions. The story presents themes of struggle, love, and justice. Rara Kuning, as the central character, is frequently portrayed as possessing both physical beauty and moral virtue. The sequence of scenes in the Wayang Timplong narrative, featuring characters such as Dewi Sekartaji, Klana Sembaja, Arya Wiguna, and Resi Darmo, demonstrates a close interrelation between aesthetic, moral, and spiritual values within Javanese tradition. Each event conveys denotative, connotative, and mythological meanings that collectively construct the narrative structure while simultaneously functioning as a medium for value transmission. Overall, the Wayang Timplong storyline is not merely a form of traditional entertainment but also a medium for moral and character education. The narrative reinforces Javanese myths emphasizing the importance of loyalty, purity, and courage in opposing destructive ambition, while simultaneously highlighting the function of traditional arts as a vehicle for character formation and the reinforcement of noble values in social life.